2013
DOI: 10.1002/jbm.b.33039
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of cyanoacrylate in intestinal and colorectal anastomosis

Abstract: Owing to the positive outcome from the porcine studies, application of CA in gastrointestinal (GI) anastomosis still seems promising. To achieve a better consistency, more methodological details need to be provided in future studies. Optimizing the dosage of CA, choice of animal model, inverted anastomosis construction, and other method details may improve intestinal and colorectal anastomoses with CA application in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
0
15
0
4
Order By: Relevance
“…While it is unclear as to why an increased reaction was seen with synthetic PEG hydrogel (other than the nature of foreign bodies), an increased inflammatory reaction is a common observation with cyanoacrylate. [6,11,12] Notably, increased inflammation was present on the serosal surface of piglet bowel at 14 days compared to 0 days with the BSP, but no comparisons have currently been performed with other sealants or controls. Therefore, it is unknown as of yet if the increased inflammation is consistent with normal healing from a sutured anastomosis or if BSP caused excess inflammation independent to normal intestinal healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is unclear as to why an increased reaction was seen with synthetic PEG hydrogel (other than the nature of foreign bodies), an increased inflammatory reaction is a common observation with cyanoacrylate. [6,11,12] Notably, increased inflammation was present on the serosal surface of piglet bowel at 14 days compared to 0 days with the BSP, but no comparisons have currently been performed with other sealants or controls. Therefore, it is unknown as of yet if the increased inflammation is consistent with normal healing from a sutured anastomosis or if BSP caused excess inflammation independent to normal intestinal healing.…”
Section: Discussionmentioning
confidence: 99%
“…Use of these products is generally limited to external surfaces due to their rigidity and propensity to cause intense local inflammation. [5,6] A surgical sealant that minimizes all of these problems and could be used internally in the human body may have large-scale clinical impact in improving surgical outcomes and minimizing the occurrence of complications in technically complex procedures such as an anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…An example is the reported successful use of N-butyl-2-cyanoacrylate for a transcatheter arterial embolization on a 57-year old patient reported to be suffering from pancreatic arteriovenous malformation (125). A recently published paper reviewed published literature studies on the use of various cyanoacrylate monomers in gastrointestinal anastomosis and correlated the methodological aspects with the experimental outcomes (126) and concluded the use of cyanoacrylates in such applications to be very promising.…”
Section: Cyanoacrylates In Medical Applicationsmentioning
confidence: 97%
“…However, from a practical point of view, our data, together with the evidence from other animal studies, have revealed the effectiveness and safety of n-butyl-cyanoacrylate as an anastomotic sealant. 30 It seems to be a promising adjuvant in a surgeon's toolbox.…”
Section: Discussionmentioning
confidence: 99%